DEVELOPMENT OF STUDENTS CHARACTERS AT PRIMARY SCHOOL THROUGH THE SEVEN-MINUTE EDUCATION (KULTUM) PROGRAM - Firman Robiansyah; Siti Nur Faizah (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract. The character of each individual is a reflection of a nation. Characters distinguish people's personalities from each other. Education is expected to be able to form an effective character because today there are many anomic behaviors that cause the moral degradation of the nation's children, including elementary school students. This study aims to describe character building habituation activities at Serang 13 Elementary School, named Kuliah Tujuh Menit (Kultum). Through this research, the researcher intends to find out the implications of the seven-minute education habituation program on fostering the character of students in Serang Public Elementary School 13 by knowing in advance the process of seven-minute education implementation and character values that appear in the habituation program. The research method used is qualitative with its type is a case study. In data collection researchers used observation, interview, documentation, and questionnaire techniques. The results showed that the seven-minute education habituation program was held every Friday morning at 7:00 a.m. to 8:30 a.m. WIB, with students fully involved in the implementation. Character values that appear in this seven-minute education activity can be known through the contents of the material presented and the process of implementation. The results are the implications of seven-minute education activities on the development of student character, can be seen from the results of questionnaires distributed to 60 respondents of research subjects, with results showing that 95.55% of respondents answered the influence of seven-minute education habituation programs, and 4.45% of respondents answered no influence. Thus the habituation of Kuliah Tujuh Menit program is highly recommended as an alternative in fostering the character of elementary school students.Keywords: Character, Students, Elementary, Kultum